A STUDY OF RELATIONSHIP BETWEEN INTERNET USAGE AND EMOTIONAL MATURITY AT HIGHER SECONDARY LEVEL (Journal of Pharmaceutical Negative Results, 2022)
Internet trend is growing day by day and the education system is going to be online sooner or later. In developing countries, like India, technological changes are rapidly taking place irrespective of age and gender. We have witnessed COVID 19, which brought technological adaptations in the education system. There was a clear shift of teaching-learning process from traditional to online. Technology is spreading out in 360 degree angle without which one cannot survive even. When it comes to the higher secondary education, how internet and other technologies can be utilized in an effective way? It is often observed adolescents are getting emotional when they watch online brutal advertisements. It is very difficult to balance their emotions once they are trolled or embarrassed in social networking sites. Such adolescents often isolate themselves from online or stop using social networking cites for some time. If we see the availability of internet, there are huge demographic differences. The students who have availability of internet are likely to access and visit online frequently compare to others. Thisstudy will help teachers to identify students with internet addiction and their emotional stability in class. The present study has gone in this direction in order to explore the relationship between availability of internet usage and emotional maturity in the students of higher secondary. A survey was conducted on 200 participants randomly and correlation was established. The findings were interesting and results were discussed.